Pengaruh Variasi Mata Gergaji terhadap Efektivitas Pemangkasan Cabang Tanaman Kopi (Coffea sp.): The Effect of Saw Blade Variations on the Effectiveness of Pruning Coffee Plant Branches (Coffea sp.) - Doddy Prima; Alwi Jaelani (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2026)
Coffee (Coffea sp.) is a strategic plantation commodity that contributes significantly to Indonesia's economy. The application of appropriate cultivation techniques—particularly pruning—is crucial for maintaining plant productivity and harvest quality. This study aimed to determine the effectiveness of using saws with varying blade specifications for pruning coffee branches. Saws serve as pruning tools for cultivated crops, including coffee; beyond enhancing labor efficiency, they also influence workplace safety in the field. Furthermore, saws are effective for pruning branches of small, medium, and large diameters. This study evaluated pruning efficiency using three tools: a saw with a 4 mm blade width, 0.5 cm blade length, and rear-facing teeth (G1); a saw with a 3.07 mm blade width, 0.7 cm blade length, and forward-facing teeth (G2); and a saw with a 3.33 mm blade width, 0.8 cm blade length, and parallel-aligned teeth (G3). These saws were used to cut branches of three different diameters: 19.93 mm (D1), 29.76 mm (D2), and 39.87 mm (D3). The results indicated that the G2 saw was the most effective in terms of time, requiring less time than G1 and G3 for cutting branches of all three diameters (D1, D2, and D3).